Identity, oppression, and diversity in archaeology : career arcs - Heath-Stout, Laura E. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Identity, Oppression, and Diversity in Archaeology documents how racism, classism, sexism, heterosexism, and ableism affect the demographics of archaeology and discusses how knowledge that archaeologists produce is shaped by the discipline's demographic homogeneity. Previous research has shown that, like many academic fields, archaeology is numerically dominated by straight white cisgender people, and those in positions of authority are predominantly men. This book examines how and why those demographic trends persist. It also elucidates how individual archaeologists' social identities shape the research they conduct, and therefore, how our demographics affect and limit our knowledge production on a disciplinary scale. It explains how, through unflinching reflection, proactive policymaking, and sincere community-building, we can build a diverse and inclusive discipline. This book will appeal to archaeologists who have an interest in diversity and inclusion within the discipline as well scholars in other disciplines who are engaged in research on diversity in academia"--
Arriving at the Trailhead : Discovering Archaeology -- The Rocky Path : Microaggressions -- Attacks Along the Trail : Harassment, Bullying, and Assault -- Landscape Formations : Systemic Inequities -- Worn Out from the Climb : The Cognitive Burden of Marginalization -- Trail Junctions : Interests, Opportunities, and Reflexivity -- Systemic Changes.
Keywords: Women archaeologists -- Employment; Archaeologists -- Employment; Archaeology -- Moral and ethical aspects; Sexism in anthropology; Racism in anthropology; Discrimination against people with disabilities; Feminist archaeology; SOCIAL SCIENCE / Archaeology